Marketing via smart speakers: what should Alexa say?. (18th May 2020) - Smith, Katherine Taken
ABSTRACT: A smart speaker is a wireless device with artificial intelligence that can be activated through voice command. The artificial intelligence interacts in the form of a virtual personal assistant, such as Amazon's "Alexa". Companies are currently creating voice applications for smart speakers that allow consumers to use the personal assistant to perform tasks, such as acquiring information and ordering products. This is the dawn of a new type of interaction between brands and consumers, a new touchpoint. Brands need to catch the vision and create content for this new technology, content that is useful in the buying process. The purpose of this study is to determine what types of marketing messages people find acceptable on smart speakers. Based on the findings, a cognitive message strategy is effective with smart speakers. The paper presents three types of executional frameworks that are best suited for the design of a cognitive message: authoritative, testimonial, and slice-of-life. The overriding requirement for marketing on smart speakers is that the message must provide value to the listener.